Helping Teens Answer the Question "Who Am I?": Gender Role and Identity Development in Male Adolescence through Early Adulthood - Rosemary V. Barnett; Stephanie Bates Galligan (EDIS)
FCS-2297, a 3-page fact sheet by Rosemary V. Barnett and Stephanie Bates Galligan, focuses on gender role as it relates to identity development in male adolescents and emerging adults. Includes references. Published by the UF Department of Family Youth and Community Sciences, May 2009.